(untitled) (Global Journal of Medical Research, 2014)
Introduction: Cardiovascular diseases are the most common cause of death and disability in both developed and developing countries. This is attributed to the stress, high incidence of hypertension and the steep rise in the metabolic parameters like blood sugars, cholesterol. Studies on the prevalence of these risk factors especially in the younger age group are warranted to study the trend and to institute guidelines for periodicity of monitoring and management. Justifying the need for routine health screening for cardiometabolic risks in young urban asymptomatic healthy individuals is the main aim of our study. Primary prevention seeks to prevent new onset atherosclerotic cardiovascular diseases (ASCVD).